Overlooked biodiversity loss in tropical smallholder agriculture. Issue 6 (1st August 2019) - Socolar, Jacob B.; Valderrama Sandoval, Elvis H.; Wilcove, David S.
Abstract: Smallholder agriculture is the main driver of deforestation in the western Amazon, where terrestrial biodiversity reaches its global maximum. Understanding the biodiversity value of the resulting mosaics of cultivated and secondary forest is therefore crucial for conservation planning. However, Amazonian communities are organized across multiple forest types that support distinct species assemblages, and little is known about smallholder impacts across the range of forest types that are essential for sustaining biodiversity. We addressed this issue with a large‐scale field inventory of birds (point counts) and trees (transects) in primary forest and smallholder agriculture in northern Peru across 3 forest types that are key for Amazonian biodiversity. For birds smallholder agriculture supported species richness comparable to primary forest within each forest type, but biotic homogenization across forest types resulted in substantial losses of biodiversity overall. These overall losses are invisible to studies that focus solely on upland (terra firma) forest. For trees biodiversity losses in upland forests dominated the signal across all habitats combined and homogenization across habitats did not exacerbate biodiversity loss. Proximity to forest strongly predicted the persistence of forest‐associated bird and tree species in the smallholder mosaic, and because intact forest is ubiquitous in our study area, our results probably represent a best‐case scenario for biodiversity in Amazonian agriculture. Land‐use planning inside and outside protected areas should recognize that tropical smallholder agriculture has pervasive biodiversity impacts that are not apparent in typical studies that cover a single forest type. The full range of forest types must be surveyed to accurately assess biodiversity losses, and primary forests must be protected to prevent landscape‐scale biodiversity loss. Abstract : Article impact statement : As smallholder agriculture follows infrastructure expansion in western Amazonia, it poses a serious threat to the region's biodiversity. Abstract : Pérdida de Biodiversidad Pasada por Alto en la Agricultura de Pequeños Propietarios Resumen: La agricultura de pequeños propietarios es la principal causa de la deforestación en la Amazonía occidental, donde la biodiversidad terrestre alcanza su máximo global. Por lo tanto, comprender el valor de la biodiversidad de los mosaicos resultantes de bosques cultivados y secundarios es crucial para para la planificación de la conservación. Sin embargo, las comunidades amazónicas están organizadas a través de múltiples tipos de bosques que soportan ensambles de especies distintas, y poco se sabe sobre los impactos de los pequeños agricultores en toda la gama de tipos de bosques que son esenciales para mantener la biodiversidad. Abordamos este problema con un inventario de campo a gran escala de aves (puntos de conteo) y árboles (transectos) en bosques primarios y agricultura de pequeños productores en el norte de Perú en 3 tipos de bosques que son clave para la biodiversidad amazónica. Para aves, la agricultura de pequeños productores soportó una riqueza de especies comparable a la de los bosques primarios dentro de cada tipo de bosque, pero la homogeneización biótica entre los tipos de bosques dio lugar a pérdidas sustanciales de biodiversidad en general. Estas pérdidas globales son invisibles para los estudios que se centran únicamente en los bosques de tierra firme. En el caso de árboles, las pérdidas de biodiversidad en bosques de tierra firme fueron dominantes en todos los hábitats combinados y la homogeneización en todos los hábitats no agravó la pérdida de biodiversidad. La proximidad a los bosques predijo robustamente la persistencia de especies de aves y árboles asociadas a bosques en el mosaico de pequeños productores, y debido a la omnipresencia de bosque intacto en el área de estudio, nuestros resultados probablemente representan el mejor escenario para la biodiversidad en la agricultura amazónica. La planificación del uso de suelo dentro y fuera de las áreas protegidas debe reconocer que la agricultura tiene impactos generalizados sobre la biodiversidad que no son evidentes en estudios que solo abarcan un solo tipo de bosque. Se debe examinar toda la gama de tipos de bosque para evaluar con precisión las pérdidas de biodiversidad, y los bosques primarios deben ser protegidos para prevenir la pérdida de biodiversidad a escala de paisaje. 摘要: 在全球陆地生物多样性最高的亚马逊西部地区, 小型农业生产是森林砍伐的主要驱动因素。因此, 了解小型农业中人工林和次生林镶嵌斑块的生物多样性价值, 对保护规划至关重要。然而, 亚马逊社区跨越了支持不同物种集合的多种森林类型, 而目前关于小型农业对维持生物多样性所必需的各种森林类型的影响研究甚少。为解决这个问题, 我们对秘鲁北部的原始林和小型农业用地中鸟类 (位点计数) 和树木 (样带) 进行了大规模的野外调查, 其中包含了对亚马逊生物多样性至关重要的三种类型的森林。对于鸟类来说, 小型农业用地维持的物种丰富度与各类型原始林相近, 但森林类型之间的生物同质化导致了总体生物多样性严重下降。然而, 只关注山地森林的研究发现不了这样的生物多样性总体丧失。对于树木来说, 山地森林的生物多样性丧失在所有生境中占主导地位, 而生境之间的生物同质化并不会加剧生物多样性丧失。与森林的距离显著地预测了小型农业镶嵌斑块中林鸟和树种的续存情况, 但由于本研究地点有广泛分布的原始林, 以上结果可能代表的是亚马逊农业生物多样性的最佳情况。进行保护地内外的土地利用规划时应认识到, 热带小型农业对生物多样性有普遍影响, 即使这一点在覆盖单一森林类型的典型研究中并不明显。因此, 未来的保护规划应全面调查各种类型的森林、准确评估生物多样性丧失, 并保护原始林以防止景观水平的生物多样性丧失。【翻译: 胡怡思; 审校: 聂永刚】